Fifty years of swine production - Koch, B.A. (Kansas Agricultural Experiment Station, 2011)
Changes in methods of feeding, breeding, and managing swine have been almost revolutionary the past 50 years. Consumer preference disease control , new knowledge concerning nutrition, new and more adaptable equipment, new structural methods, improved breeding techniques and specialize management all have contributed to the changes in swine production.
Keywords: Swine; Disease control; Feeding; Breeding